2019
DOI: 10.1111/jog.13960
|View full text |Cite
|
Sign up to set email alerts
|

The ratio of cavum septi pellucidi width to anteroposterior cerebellar diameter: A novel index as a diagnostic adjunct for prenatal diagnosis of trisomy 18

Abstract: Aim To explore the effectiveness of cavum septi pellucidi (CSP) width to anteroposterior cerebellar diameter (APCD) ratio as a diagnostic adjunct for prenatal diagnosis of trisomy 18. Methods Images of normal fetal brain within 15 and 35 weeks were stored in our center from 2016 to 2017. Images of aneuploid fetuses were retrospectively collected from 2004 to 2017. The transverse cerebellar diameter, APCD and CSP width were measured. CSP/APCD and APCD/transverse cerebellar diameter ratios were calculated and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Of the 32 papers, 6 were excluded from further review. The remaining 26 articles 4–13,15,17,18,20–22,24,25,27,30,31,33,44,45 were reviewed qualitatively (Tables 1 and 2) and of these, 10 were included for quantitative review 4,5,7,9,12,15,21,24,30,33 . We contacted the corresponding author of all of the articles excluded for quantitative review due to the way in which the data were reported (eg, only graphically or not reported by gestational age); however, only one author sent us data suitable for analysis 24 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 32 papers, 6 were excluded from further review. The remaining 26 articles 4–13,15,17,18,20–22,24,25,27,30,31,33,44,45 were reviewed qualitatively (Tables 1 and 2) and of these, 10 were included for quantitative review 4,5,7,9,12,15,21,24,30,33 . We contacted the corresponding author of all of the articles excluded for quantitative review due to the way in which the data were reported (eg, only graphically or not reported by gestational age); however, only one author sent us data suitable for analysis 24 …”
Section: Resultsmentioning
confidence: 99%
“…The remaining 26 articles [4][5][6][7][8][9][10][11][12][13]15,17,18,[20][21][22]24,25,27,30,31,33,44,45 were reviewed qualitatively (Tables 1 and 2) and of these, 10 were included for quantitative review. 4,5,7,9,12,15,21,24,30,33 We contacted the corresponding author of all of the articles excluded for quantitative review due to the way in which the data were reported (eg, only graphically or not reported by gestational age); however, only one author sent us data suitable for analysis. 24 Characteristics of Studies Included for Quantitative Synthesis: CC There were seven included articles for the CC, of which two and five used 3D and 2D measurements, respectively.…”
Section: Eligibility Criteria and Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study examined the efficacy of the ratio of CSP width to anterior-posterior cerebellar diameter (APCD) as a diagnostic tool for prenatal trisomy 18 diagnosis. 22 A higher CSP/APCD ratio would support the diagnosis, especially in cases with trisomy 18 syndrome with few abnormalities. The strength of our study is that we have presented the CSP width/BPD ratio, a new practical and gestational weekindependent marker to predict aneuploidy.…”
Section: Discussionmentioning
confidence: 99%